Synthesis Chitosan from Squid Pens Waste - Sanuddin, Mukhlis; Yulianis, Yulianis; Annisaq, Nur (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2020)
Squid is one of the fisheries commodities that is quite important and ranks in the third position after fish and shrimp. Still, many people don't know that these animals have bones that usually discarded when processing squid meat. Squid pens used as a source of medicinal ingredients, one of which is chitosan. Chitin was obtained by deproteination process with 3.5% (w/v) NaOH, and demineralization with 1 M HCl. Chitosan was obtained from the chitin deacetylation process using a variation of 50% (w/v) NaOH and 60% (w/v) NaOH. In this research, chitosan only produced use method 60% acetylation degree. Chitosan compounds obtained from the deacetylation process, with 60% NaOH were analyzed using FTIR spectrophotometers, received functional groups: C-H, O-H, N-H, and NH2.